Sustainable recovery of rare earth elements from granite: A review of modern techniques (Journal of the Asiatic Society of Bangladesh, Science, 2026)
The extraction of Rare Earth Elements (REEs) is important for clean energy, electronics, and high-tech materials. While minerals like monazite and bastnäsite are the main sources, granite is also being studied as a backup source because it contains REE-rich minerals such as apatite, zircon, and allanite. But extracting REEs from granite is difficult due to its hardness, low REE content, and radioactive materials, which make separation and recovery more complex. This paper reviews different extraction methods, including standard physical processes, bio-based techniques, and newer, greener methods like using ionic liquids. Additionally this study also reviews the importance of finding cleaner, more efficient ways to recover REEs from granite, focusing on better results with less harm to the environment. The findings show that pre-treatment with microwaves reduces the strength of the rock, making it easier to process, and acid leaching after this treatment improves the REE extraction rate.J. Asiat. Soc. Bangladesh, Sci. 51(2): 193-206, December 2025